2019
DOI: 10.4102/sajip.v45i0.1595
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary development of the Higher Education Hindrance Demands Scale amongst academics in the South African context

Abstract: Orientation: Over the past two decades, since the advent of democracy in South Africa, the country has undergone transformation in virtually all sectors of society. Education is no exception, with higher education institutions (HEIs) also experiencing change. The transformation of HEIs has brought about many new challenges, demands and stresses that may hinder the work performance of academics.Research purpose: This study seeks to determine the ‘hindrance demands’ unique to the South African context by develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 82 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…Out of the six studies that were reviewed, only three of the studies indicated their sampling technique. This included non-probability sampling (Dhanpat et al, 2019), convenience (Mudrak et al, 2018) and also stratified sampling (Han et al, 2019), whilst the other three studies made no mention of their sampling method. All studies that were conducted was done in an academic environment i.e.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the six studies that were reviewed, only three of the studies indicated their sampling technique. This included non-probability sampling (Dhanpat et al, 2019), convenience (Mudrak et al, 2018) and also stratified sampling (Han et al, 2019), whilst the other three studies made no mention of their sampling method. All studies that were conducted was done in an academic environment i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Emotional demands is about being able to deal with strong feelings such as distress, anger, anxiety, and frustration in the workplace (Mazzetti, Guglielmi & Topa, 2011 (Dhanpat et al, 2019) Decolonisation Organisational demand…”
Section: Emotional Demands Qualitative Demandmentioning
confidence: 99%
See 3 more Smart Citations